Factors Associated with Days Alive and at Home within 30 Days (DAH30) Scores Following Surgery: A Systematic Review - Jenna Bartyn; James Morkaya; Sascha Karunaratne; Tian You Chen; Michael Solomon; Cherry Koh; Charbel Sandroussi; Daniel Steffens (Gastrointestinal Disorders, 2024)
Background/Objectives: Days Alive and at Home within 30 days (DAH30) is a patient-centred measurement tool designed to assist with the decision-making and management of patients undergoing surgery. Thus, identifying factors associated with better DAH30 scores would support healthcare providers to optimise patient care and outcomes. This systematic review aimed to determine factors associated with DAH30 scores following surgery. Methods: A sensitive electronic search was conducted in MEDLINE, Embase, Scopus, Web of Science and CINAHL databases in September 2022. Eligible studies included patients undergoing surgery and reporting the association of preoperative and/or postoperative factors and DAH30. Risk of bias was assessed using the QUIPs tool. Results: Of the 14 studies identified, the majority (n = 13, 93%) were cohort studies, presenting moderate or high (n = 8, 60%) risk of bias. This review identified a number of factors influencing DAH30 scores in patients undergoing surgery. ASA Physical Status and surgery duration were the most common factors influencing DAH30 scores. Conclusions: Optimising patients’ health prior to surgery and reducing surgical time have the potential to improve patients’ recovery.